2022
DOI: 10.4102/safp.v64i1.5534
|View full text |Cite
|
Sign up to set email alerts
|

Late-life depression and the family physician

Abstract: Late-life depression (LLD) is a common disorder seen in clinical practice. Depression in this population group is often left undetected and untreated. The majority of elderly individuals who seek help present to the primary health care setting. The family physician is ideally placed to screen for symptoms of LLD, given that they often have longitudinal knowledge of the patient’s history, premorbid personality, functioning and overall health status. An understanding of risk factors, differential diagnoses, appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…In the current study, the most common symptom for the referral was a suicidal risk at about 97.7%, psychotic symptoms at 96.9%, harm to others at 96.2%, and lastly poor response to treatment at 94.6%. Similar components for referral to psychiatrists were observed in the South African Family Medicine practice [10]. In contrast to the present study findings, a study conducted among tertiary care settings revealed that about 56.6% of patients were referred due to suicidal risk and 91.6% of patients were referred due to substance abuse [28].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In the current study, the most common symptom for the referral was a suicidal risk at about 97.7%, psychotic symptoms at 96.9%, harm to others at 96.2%, and lastly poor response to treatment at 94.6%. Similar components for referral to psychiatrists were observed in the South African Family Medicine practice [10]. In contrast to the present study findings, a study conducted among tertiary care settings revealed that about 56.6% of patients were referred due to suicidal risk and 91.6% of patients were referred due to substance abuse [28].…”
Section: Discussionsupporting
confidence: 54%
“…By understanding these underlying factors, healthcare providers can tailor treatment approaches effectively [5]. Therefore, improving primary healthcare physicians' (PCPs') diagnostic capacity and knowledge, reducing stigma, and providing access to evidence-based treatment are critically necessary to increase the quality of life and medical results measures in the elderly population [10]. In a cross-sectional study conducted in the Riyadh region, 180 non-psychiatrist physicians were assessed for their knowledge and attitudes regarding psychiatric disorders, including depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Среди видов депрессии особую проблему представляет депрессия позднего возраста, которая возникает после 60 лет. Уровень ее распространенности в учреждениях первичной медико-санитарной помощи составляет 6-9% [3]. Однако есть исследования, показавшие гораздо более высокие цифры.…”
unclassified